2020
DOI: 10.1093/gji/ggaa318
|View full text |Cite
|
Sign up to set email alerts
|

From space to lithosphere: inversion of the GOCE gravity gradients. Supply to the Earth’s interior study

Abstract: SUMMARY The emergence of high resolution satellite measurements of the gravitational field (GOCE mission) offers promising perspectives for the study of the Earth’s interior. These new data call for the development of innovant analysis and interpretation methods. Here we combine a forward prism computation with a Bayesian resolution approach to invert for these gravity gradient data configuration. We apply and test our new method on satellite data configuration, that is 225 km height with a glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It provides important information about the geological development, which was previously hidden under an ice sheet several kilometres thick (Ferraccioli et al 2011;Fretwell et al 2013;Hirt 2014;McKenzie et al 2015). The specific value of gravity gradients is shown in Ebbing et al (2018), Sebera et al (2018), Plasman et al (2020).…”
Section: Scientific Resultsmentioning
confidence: 99%
“…It provides important information about the geological development, which was previously hidden under an ice sheet several kilometres thick (Ferraccioli et al 2011;Fretwell et al 2013;Hirt 2014;McKenzie et al 2015). The specific value of gravity gradients is shown in Ebbing et al (2018), Sebera et al (2018), Plasman et al (2020).…”
Section: Scientific Resultsmentioning
confidence: 99%
“…Plasman inverted the six tensor components of GOCE gravity gradient data and concluded that the simultaneous inversion of several components displayed a significant improvement for the global tensor recovery. The proposed method was successfully verified in complex subduction cases with gradient and gravity data [15]. Residual errors in the terrain correction could lead to errors in data interpretation.…”
Section: Introductionmentioning
confidence: 95%